Knowledge and attitudes of paediatric dentists in Turkey regarding cone beam computed tomography (CBTC) - Orhan, Ayşe Işıl; Cesur, Emre; Bezgin, Tuğba; Orhan, Kaan (Cumhuriyet University Faculty of Dentistry, 2021)
Objectives: The use of cone-beam computed tomography (CBCT) in dental practice has increased in recent years due to the lower radiation dose, fast scanning time, and superior imaging quality compared to conventional computed tomography (CT). Although CBCT is frequently preferred for the evaluation of the craniofacial region in areas such as orthodontics, orthognathic surgery, head trauma, and implant surgery, its use is still limited in paediatric dentistry. The aim of this study was to evaluate the knowledge and attitudes of paediatric dentists in Turkey regarding CBCT. Materials and Methods: A self-administered anonymous questionnaire consisting of 17 questions was completed by 273 volunteer participants. Of these, 135 were postgraduate students in a paediatric dentistry program and 137 were PhDs or specialists. Relationships between categorical variables were evaluated using chi-square test. Results: 237 (86.8%) of the 273 participants stated that they were knowledgeable about CT/CBCT, but 81% of the respondents said the information they received during dental education was insufficient. The only significant relationship among the studied variables was between the participants’ self-rated knowledge about the use of CT and/or CBCT for the dentomaxillofacial region and the institution in which they worked (P =.001). Conclusions: Although our results indicate that paediatric dentists have high levels of knowledge and positive attitudes towards digital imaging techniques and CBCT, it would be beneficial to update the dental curricula and enable dental students to gain practical experience in addition to theoretical knowledge.

Amaç: Konik ışınlı bilgisayarlı tomografilerin (KIBT) diş hekimliğinde kullanımı son yıllarda oldukça yayılmaktadır. KIBT; ortodontide, ortognatik cerrahide, kafa travmalarında ve implant cerrahisinde, kraniyofasiyal bölgenin değerlendirilmesinde oldukça sık kullanılsa da, pedodontide kullanımı halen sınırlıdır. Bu çalışmanın amacı, Türkiye’de pedodontistler arasında KIBT kullanımına yönelik bilgi ve tutumun değerlendirilmesidir. Gereç ve Yöntemler: Bu çalışma 273 gönüllü katılımcı ile gerçekleştirilmiş olup, katılımcılardan kendi kendine yönetilen ve 17 sorudan oluşan bir anketi isimsiz olarak doldurmaları istenmiştir. Katılımcıların 135’ini doktora/uzmanlık öğrencileri oluştururken, 137’si pedodonti doktoru ve/veya uzmanıdır. Bu araştırmada, kategorik değişkenler arası ilişkilerin incelenmesinde chi-kare testi kullanılmıştır. Bulgular: 237 (%86,8) katılımcı BT/KIBT hakkında bilgi sahibi olduğunu belirtmiştir. Katılımcıların %81’i diş hekimliği eğitimi sırasında aldıkları bilginin yetersiz olduğunu bildirmiştir. Değişkenler arası bağımlılık değerlendirildiğinde, anlamlı tek fark, katılımcıların BT/KIBT kullanımı konusunda bilgi sahibi olup olmadıklarına dair soru ile çalıştıkları kurum arasında bulunmuştur (P =,001). Sonuçlar: Çalışmamızın sonuçları, pedodontistlerin dijital görüntüleme yöntemleri ve KIBT kullanımına dair yüksek bilgiye sahip olduklarını ve olumlu tutum gösterdiklerini saptasa da, diş hekimliği müfredatının güncellenmesi ve öğrencilerin teorik bilginin yanı sıra pratik tecrübe edinmelerinin sağlanması, KIBT kullanımının yaygınlaşması ve yerinde kullanımının sağlanması açısından faydalı olacaktır.
Keywords: Attitude; CBCT; Digital Imaging Methods; Knowledge; Pediatric Dentistry; Pedodonti; KIBT; Dijital Görüntüleme Metodlaro; Bilgi Tutum